PERANCANGAN IDENTITAS VISUAL KAMPUNG KERAMIK DINOYO MALANG - Mahendra Wibawa (Lembaga Penelitian Pengembangan dan Pengabdian Kepada Masyarakat STMIK Asia Malang, 2019)
This research aims to produce a visual identity for the Dinoyo Malang ceramic village. Data was collected through interview methods and document studies analyzed by the S.W.O.T method. This design produced a GSM (Graphic Standard Manual) that contained the Dinoyo ceramic village logo, tagline, along with two characters Kerama and Krani as the mascot of the village.